Safety and efficacy of daptomycin in outpatient parenteral antimicrobial therapy: a prospective and multicenter cohort study (DAPTODOM trial). Issue 3 (4th March 2017) - Cervera, Carlos; Sanroma, Pedro; González-Ramallo, Víctor; García de la María, Cristina; Sanclemente, Gemma; Sopena, Nieves; Pajarón, Marcos; Segado, Antonio; Mirón, Manuel; Antón, Francisco; Basterretxea, Andima; Cuende, Ana; et al.
Abstract: Background: Daptomycin is an optimal choice for outpatient parenteral antibiotic therapy (OPAT) because of its safety, once-daily administration and its activity against Gram-positive bacteria. Although daptomycin is increasingly being used in OPAT, limited information about its safety in this scenario is available. Methods: We performed a prospective multicentre pilot study to evaluate the safety of daptomycin in outpatients with proved or suspected Gram-positive infections (DAPTODOM). The primary objective was to evaluate the safety and the secondary objective to evaluate the efficacy in OPAT. We also looked at the development of daptomycin resistance in those cases with microbiological failure. Results: We included 54 patients from 12 Spanish hospitals, 67% male with a mean age of 67.1 years. Most patients (87%) had chronic underlying diseases. The main reason for inclusion was skin and soft-tissue infections in 52%, followed by bacteremia or endocarditis in 34%. Staphylococcus aureus accounted for 44% of the isolates (24% were methicillin-resistant), coagulase-negative staphylococci 15% and enterococci 7%. Two patients (4%) had to be readmitted because of complications; only one patient had an adverse effect related to daptomycin (increase in serum creatine kinase levels), which disappeared after discontinuation (2%). At the end of follow-up, 96% of patients had good outcome and only 4% of patients did not have a clinical or microbiological cure. The use of a 2-minute bolus in 18 cases was not associated with adverse effects. Conclusions: Daptomycin was safe and efficacious in outpatients with Gram-positive bacterial infections and can be administered in 2-minute bolus infusion.